ETHNOMATHEMATICS STUDY OF PRAMBANAN RAMAYANA BALLET AND THE APPLICATION OF CONTEXT IN MATHEMATICAL PROBLEMS - Monica Tiara Gunawan; Hongki Julie; Marcellinus Andy Rudhito (Sanata Dharma University Yogyakarta, 2025)
This research aimed to describe the history of Ramayana Ballet Prambanan performances, the performance of the second half of the AnomanObong scene, the philosophical meaning and characteristics of the second half of AnomanObong, the training of dancers of the second half of AnomanObong, and the fundamental activity of mathematics in the second half of AnomanObong. This qualitative research examined ethnomathematics in the cultural context of Ramayana Ballet Prambanan. Data were collected through observation, interviews, and documentation, with validation through experts and triangulation of sources and techniques. Data analysis included data reduction, presentation, and conclusion drawing. The results showed five mathematical activities in the history of Ramayana Ballet Prambanan, namely counting, locating, measuring, playing, and explaining. There are five mathematical activities in the second half performance of AnomanObong, namely: counting, locating, measuring, designing, and explaining. There existed four mathematical activities in the philosophical meaning of the second act of AnomanObong, namely counting, locating, designing, and explaining. The counting, locating, and measuring activities were present in all data classes and can be used for learning mathematics in the domains of numbers, algebra, geometry, and measurement. The designing activity was only present in the second, third, and fourth data classes, and can be applied in math learning.